2020
DOI: 10.1080/23254823.2020.1788963
|View full text |Cite
|
Sign up to set email alerts
|

Domesticating startup culture in Finland

Abstract: In recent years, startup entrepreneurship-understood not only in economic but also in cultural terms-has become increasingly important for nations' economic growth. This article examines startup culture as a global form and its domestication in local contexts. I analyse how startup entrepreneurship is made sense of in Finnish society, utilising Finnish startup guidebooks and non-fiction literature as research material. As a theoretical framework, I draw on the literatures of domestication of global trends and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The study by Koskinen (2021) revealed that the domestication of start-up culture is found in a combination of start-up entrepreneurship and culture, suggesting that certain cultures hinder start-up entrepreneurship. Pulat (2020) suggested that leadership should incorporate appropriate human-centered cultural midst by reflecting on six foundation human drives: ownership, meaning, belonging, collaboration, participation, and rituals.…”
Section: Cultural Value Theorymentioning
confidence: 99%
“…The study by Koskinen (2021) revealed that the domestication of start-up culture is found in a combination of start-up entrepreneurship and culture, suggesting that certain cultures hinder start-up entrepreneurship. Pulat (2020) suggested that leadership should incorporate appropriate human-centered cultural midst by reflecting on six foundation human drives: ownership, meaning, belonging, collaboration, participation, and rituals.…”
Section: Cultural Value Theorymentioning
confidence: 99%
“…Start-ups are perceived as having a culture characterized by competitiveness, self-interest, hard work, creativity, sharing, acceptance of failure, appreciation of risk-taking (Maas and Ester, 2016;Koskinen, 2020); and a willingness to risk losses (Koudstaal et al, 2016). The startup culture is regarded as inherently masculine, with women stereotypically viewed as riskaverse (Brindley, 2005).…”
Section: Entrepreneurship Academia and Gendermentioning
confidence: 99%
“…These qualities tend to have negative connotations in the Finnish context, which might be the reason why the students voice a preference for traditional SME entrepreneurship, which is more associated with hard work. (Koskinen, 2020. ) This is acknowledged in the discussions: 'startup entrepreneurs work in a sort of bubble, like "we're doing something great here," and outside people are giggling at them.…”
Section: Critical Whisperingmentioning
confidence: 99%
“…Economic uncertainty and responsibilities related to entrepreneurship are pondered, and thus 'the jump to the unknown scares ' them (Discussant2, 2018). Sceptical reasoning appears as an interesting contrast to the desire to increase innovative and risky growth entrepreneurship among the highly educated population, which is visible in policy agendas (see Koskinen, 2020) and an important justification for the startup course.…”
Section: Critical Whisperingmentioning
confidence: 99%